Determination of Information Technology Utilization in Local Regulation Enforcement - Rina Wahyuni (Al-Makki Publisher, 2026)
The rapid development of digital technology has encouraged government institutions to implement digital transformation in order to improve the effectiveness and efficiency of public services. In the context of regional regulation enforcement, the Civil Service Police Unit (Satuan Polisi Pamong Praja / Satpol PP) plays a strategic role in maintaining public order and ensuring legal compliance within regional governance. However, the utilization of information technology within Satpol PP institutions is still influenced by several factors, including digital transformation, employee knowledge, and organizational readiness. This study aims to analyze the influence of digital transformation, knowledge, and organizational readiness on the utilization of information technology in supporting the enforcement of regional regulations within the East Java Provincial Satpol PP. The research employed a quantitative approach using survey methods. Data were collected through questionnaires distributed to 66 Satpol PP employees selected using random sampling. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS software. The results show that digital transformation and organizational readiness have a significant positive influence on the utilization of information technology. Meanwhile, knowledge does not significantly affect the adoption of information technology. Organizational readiness was found to be the most dominant factor influencing technology utilization within the institution. This study concludes that strengthening digital transformation strategies and improving organizational readiness are essential for optimizing the use of information technology in supporting effective and responsive enforcement of regional regulations.